Laparoscopic Treatment of Obese Patients with Gastroesophageal Reflux Disease and Barrett S Esophagus: A Prospective Study - Chacon-Pacheco, M (2012)
Background: Short-segment Barrett s esophagus (SSBE) or long-segment Barrett s esophagus (LSBE) is the consequence of chronic gastroesophageal reflux disease (GERD), which is frequently associated with obesity. Obesity is a significant risk factor for the development of GERD symptoms, erosive esophagitis, Barrett s esophagus, and esophageal adenocarcinoma. Morbidly obese patients who submitted to gastric bypass have an incidence of GERD as high as 50% to 100% and Barrett s esophagus reaches up to 9% of patients. Methods: In this prospective study, we evaluate the postoperative results after three different procedures-calibrated fundoplication+posterior gastropexy (CFPG), fundoplication+vagotomy+distal gastrectomy+Roux-en-Y gastrojejunostomy (FVDGRYGJ), and laparoscopic resectional Roux-en-Y gastric bypass (LRRYGBP)-among obese patients. Results: In patients with SSBE who submitted to CFPG, the persistence of reflux symptoms and endoscopic erosive esophagitis was observed in 15% and 20.2% of them, respectively. Patients with LSBE were submitted to FVDGRYGJ or LRRYGBP which significantly improved their symptoms and erosive esophagitis. No modifications of LESP were observed in patients who submitted to LRRYGBP before or after the operation. Acid reflux diminished after the three types of surgery were employed. Patients who submitted to LRRYGBP presented a significant reduction of BMI from 41.5±4.3 to 25.7±1.3 kg/m 2 after 12 months. Conclusions: Among patients with LSBE, FVDGRYGJ presents very good results in terms of improving GERD and Barrett s esophagus, but the reduction of weight is limited. LRRYGBP improves GERD disease and Barrett s esophagus with proven reduction in body weight and BMI, thus becoming the procedure of choice for obese patients. © Springer Science+Business Media, LLC 2012.